Shaping APEC: Perspectives from the Philippines - Erlinda M. Medalla; Jenny D. Balboa (Philippine Institute for Development Studies (PIDS), 2007)
APECs vision of integrating the APEC has remained, for the most part, intangible. Cultural differences, socioeconomic disparity, and lack of a defined structure and leadership have been cited by many as major obstacles. Lately, there has been a proliferation of regional groups in Asia, creating an impression that APEC is no longer a priority for its members. Thus, various inquests into APECs role and relevance in the Pacific region have come to fore. Several options and strategies has been presented to reshape APEC and transform it into a much more relevant, responsive, viable, and cohesive regional group. These options range from a reevaluation of the APEC agenda, to administrative improvements and more radical changes. What kind of role has APEC played that has particularly benefited developing countries like the Philippines? What else could be done to make APEC more effective as a key player in the global economy and a vehicle for countries in the Pacific Region to maximize economic gains in a multilateral trading environment? This short paper provides a perspective on how APEC should be shaped from the point of view of a developing economy member, particularly the Philippines.
Keywords: 330; World Trade Organization; ASEAN; regional integration; APEC; free trade area; developing countries; Regionale Wirtschaftsintegration; Freihandelszone; Internationale Wirtschaftsbeziehungen; Entwicklungsländer; Philippinen